Potential Activity of Caryophyllene Derivatives as Xanthine Oxidase Inhibitor: An in silico Quantitative Structure-Activity Relationship Analysis - Arif Setiawansyah; Baiq Maylinda Gemantari (Journal of Food and Pharmaceutical Sciences, 2022)
As the enzyme responsible for the uric acid formation, Xanthine oxidase was considered to be a therapeutic target for hyperuricemic treatment. This study was carried out to assess the potential of caryophyllene, and its derivates usually present in the natural product to inhibit Xanthine oxidase. The molecular docking using Autodock Tool and Biovia Discovery Studio was conducted to visualize the molecular interaction and to reveal the structure-activity relationship of those compounds. The results showed that the derivates of caryophyllene showed a higher affinity to Xanthine Oxide than Allopurinol. Among those all, caryophyllene oxide has the most stable bonding to xanthine oxide. Structure-activity relationship analysis showed that the chemical properties of the compound affected the affinity and molecular interaction to the enzyme as the target site in this study. The number of double bonds, substituents position, conformational structure related to steric hindrance, and the presence of lactone ring were assumed to influence the xanthine oxide inhibitory activity of caryophyllene derivates.